Anxiety, stress, and related factors in pregnant women during the COVID-19 pandemic in Hospital Universiti Sains Malaysia - Jasni, Nurshazwani (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2022)
Pregnant mothers with anxiety and stress are due to many factors. Thus, this study aims to assess the level of anxiety and stress level and their associated factors among pregnant women. A cross-sectional study was conducted in Obstetrics and Gynaecology (O&G) clinic in Hospital Universiti Sains Malaysia from January 2022 to April 2022. A self-administered questionnaire involving 207 respondents between 19-44 years old and who fulfilled the inclusion criteria were selected as the study's respondents. The sampling method uses simple random sampling methods based on sampling and sample exclusion criteria. The data in this study is analyzed using Statistical Package for Social Sciences (SPSS) version 26 software. This study revealed the level of anxiety that pregnant women were low anxiety 116(56%), mild anxiety 78(37.7%), and high anxiety 13(6.3%). Meanwhile, the stress level was low, 125(60.4%) and 82(39.6%) moderate stress. The result has shown that employment status, educational level, and physical exercise were not significantly associated with anxiety (p> 0.05). Meanwhile, employment status was significantly associated with stress levels. Also, this study's educational level and physical exercise were not significant, with a p-value >0.05. The result of this study may be used for learning purposes. Health education can be given directly to pregnant women after getting consent